Pien Tze Huang Alleviates Relapsing-Remitting Experimental Autoimmune Encephalomyelitis Mice by Regulating Th1 and Th17 Cells - Qiu, Xuemei; Guo, Qingqing; Liu, Xue; Luo, Hui; Fan, Danping; Deng, Yongqi; Cui, Hua; Lu, Cheng; Zhang, Ge; He, Xiaojuan; Lu, Aiping (Frontiers in Pharmacology, 2018)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS), characterized by infiltrating inflammatory cells and demyelinating lesions, and T helper (Th) cells play critical roles in the pathogenesis of MS. There is still lack of effective treatments currently. Pien Tze Huang (PZH), a traditional Chinese medicine formula, has been proved to have anti-inflammatory, neuroprotective and immunoregulatory effects. However, whether PZH can be used to treat MS is still obscure. This study aimed to investigate the possible therapeutic effect and the underlying action mechanism of PZH in relapsing-remitting experimental autoimmune encephalomyelitis (RR-EAE) mice. Female SJL/J mice were immunized with myelin proteolipid protein 139-151 (PLP139–151) and pertussis toxin to establish RR-EAE model. Mice were then randomly divided into normal group, model group, PZH group and positive control group (fingolimod, FTY-720), and drugs were orally administered for 60 days from the day 10 after immunization. Sera of mice were collected for ELISA detection. Tissues of CNS were harvested for hematoxylin-eosin (H-E) and luxol fast blue (LFB) staining. Furthermore, Th1, Th17 cells and their related cytokines in the CNS were detected by flow cytometry and quantitative real-time PCR, respectively. Proteins involved in STAT and NF-κB signaling pathways were detected by western blot. The results showed that PZH-treated mice displayed mild or moderate clinical symptoms compared with untreated EAE mice that exhibited severe clinical symptoms. PZH remarkably reduced inflammatory cell infiltration and myelin damage in the CNS of EAE mice. It markedly down-regulated the levels of IFN-γ and IL-17A in sera of EAE mice. Moreover, PZH could reduce the percentages of Th1 and Th17 cells. It also suppressed the production of transcription factors ROR-γt and T-bet as well as the mRNA levels of their downstream pro-inflammatory cytokines, such as IFN-γ and IL-17A. Furthermore, PZH could inhibit the phosphorylation of some key proteins in the STAT and NF-κB signaling pathways. In conclusion, the study demonstrated that PZH had a therapeutic effect on RR-EAE mice, which was associated with the modulation effect on Th1 and Th17 cells.